Schubert's late Lieder: Beyond the song-cycles - Youens, Susan (Cambridge Cambridge University Press, 2002)
This study includes selected songs for voice and piano composed by Schubert between 1822 and his death on November 19, 1828. Schubert was diagnosed with syphilis circa late 1822, and many of the songs discussed were written with his knowledge of impending death. It is possible to discover within them a late song style, full of elegiac references to Schubert's other death-haunted works and marked by distinctive variation techniques. Youens also introduces six of the poets whose texts were set to music by Schubert